log log x = 1

Let us assume that :

log x = y

Now substitute into the equation:

log (log x) = 1

==> log y = 1

Now we will rewrite:

==> y = 10^1 = 10

But we know that :

log x = y

==> log x = 10

**==> x= 10^10 **

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now